Correlation of the position of the anal dimple with the caudal termination of the striated muscle complex in patients with anorectal malformations - Amit Kumar; Vipan Bangar; Niyaz Ahmed Khan; Jigar N Patel; Amit Gupta; Partap Singh Yadav; Rajiv Chadha; Subhasis Roy Choudhury (Wolters Kluwer Medknow Publications, 2022)
Background: In children with anorectal malformations (ARM), the vertical fibres of the striated muscle complex (SMC) are believed to be located within the limits of the anal dimple (AD). Methods: Forty five cases of ARM underwent posterior sagittal anorectoplasty (PSARP), median age 8.5 months. During PSARP the anterior, posterior limits and midpoint of the AD and SMC were marked. The location of AD was correlated with SMC. Results: A 'well developed' AD and SMC was seen in 80 % and 86.7 % patients respectively. The mean width of the AD and SMC was more in females than in males (20.96 vs. 18.98 mm and 14.24mm vs. 13.45mm respectively). In 36 cases (80 %), across the spectrum of ARM, the SMC was posterior in relation to the AD. In 7 cases (15.5 %) it correlated in position with the AD and in 2 cases (4.44 %), it was anterior to the AD. Conclusions: In the majority of cases AD and SMC were 'well developed' and the location of the SMC does not correlate with that of the AD. This has significant practical value in the important step of optimizing the placement of the rectum through the center of the SMC during repair.